Sentinel surveillance data from Eritrean migrants in Italy: The theory of "Healthy Migrants". Issue 22 (March 2018) - Ciccozzi, Massimo; Cella, Eleonora; Ceccarelli, Giancarlo; Vita, Serena; Dicuonzo, Giordano; Lopalco, Maurizio; Antonelli, Francesca; Conti, Alessia; Ottaviani, Rossella; De Cesaris, Marina; Spoto, Silvia; Angeletti, Silvia
Abstract: Background: Eritrean migrants accounted for the majority of people who drowned in the Mediterranean this year. Recently, data deficit about international migration has been reported. Methods: One hundred and thirty-three Eritrean migrants, upon their arrival in Italy, were accommodated at the asylum seekers center of Castelnuovo di Porto, together with 25 sanitary workers, and received microbiological surveillance at the Clinical Pathology and Microbiology Unit of the University Campus Bio-Medico of Rome. Results: Gram-negative bacteria, mostly Klebsiella pneumoniae and Klebsiella oxytoca, were frequently recovered in surveillance swabs. Gram-positive bacteria, represented by Streptococcus pneumoniae, Streptococcus pyogenes, Streptococcus dysgalactiae and Staphylococcus aureus, were also isolated in surveillance swabs. In migrants, polymicrobial swabs were recovered at high frequency, and unusual microorganisms, rarely found in our country, were isolated. Conclusion: The polymicrobial colonization and the high prevalence of gram-negative bacteria represent the baseline characteristics of this migrant population from Eritrea. The presence of unusual microorganisms can be potentially pathogenic to asymptomatic carriers at risk of developing clinical disease if immunosuppressed or subjected to invasive procedures. In conclusion, active microbiological surveillance can represent an advantage for the host country in terms of data collection and by tracing unusual or resistant microorganisms by monitoring migrants' health status.